Fractal degassing from Erebus and Mayon volcanoes revealed by a new method to monitor H2O emission cycles - Aggangan, Brian (2015)
Many active volcanoes around the world release passively large amounts of gas between eruptions. Monitoring how these gas emissions fluctuate over time is crucial to infer the physical processes occurring within volcanic conduits and reservoirs. Here we report a new method to capture remotely the spectral properties of the emissions of H2O, the major component of most volcanic plumes. The method is based on a new theoretical model that correlates the volcanogenic water content of condensed volcanic plumes with the intensity of the light scattered by the droplets moving with the gas. In turn, we show that light intensity of the plume, and thus steam pulses time series, can be obtained with a proper analysis of digital images. The model is experimentally validated by generating condensed plumes with an ultrasonic humidifier, and then the method is applied to the gas plumes of Erebus and Mayon volcanoes. Our analysis reveals three main features: (1) H2O time series are composed of numerous periodic components of finite duration; (2) some periodic components are common in H2O and SO2 time series, but others are not; and (3) the frequency spectra of the H2O emissions follow a well-defined fractal distribution, that is, amplitude (Δ) and frequency (ν) are correlated by means of power laws (Δ ∝ νγ), with exponent γ ≈ − 1 for Erebus and for Mayon. These findings suggest that quiescent degassing emerges from the complex coupling between different processes occurring within magma plumbing systems. Our method is ideal for real-time monitoring of high-frequency H2O cycles at active volcanoes.